Theoretical investigation on acetylene cyclotrimerization catalysed by TiO2 and Ti. (31st January 2019) - Deng, Zhe‐Peng; Wang, Yong‐Cheng; Mou, Dan; Sun, Yu; Da, Hu; Gao, Jian‐De
Abstract: The reaction mechanisms for acetylene cyclotrimerization using TiO2 and Ti catalysts were studied by the density functional theory (DFT) method. Interestingly, the reaction catalysed by TiO2 occurs on the potential energy surface (PES) with a singlet state. For the same reaction catalysed by Ti, spin‐orbit coupling (SOC) calculations were performed to discuss spin inversion between the triplet and singlet PESs. The chance that an electron hops in the vicinity of the minimum‐energy crossing point (MECP) was verified regarding the Landau‐Zener model. The possibilities of single ( P 1 ISC ) and double ( P 2 ISC ) at MECP1 (SOC = 253.38 cm −1 ) are about 0.35 and 0.46, respectively. The energetic span model developed by Kozuch was applied in the above reactions. The turnover frequency (TOF)‐determining transition state (TDTS) and TOF‐determining intermediate (TDI) were verified. The TOF value indicates that Ti is a more active catalyst compared with TiO2 in C2 H2 cyclotrimerization. Abstract : The reaction mechanisms for acetylene cyclotrimerization using TiO2 and Ti catalysts were studied by density functional theory method. The turnover frequency (TOF) value indicates that Ti is a more active catalyst compared with TiO2 on the C2 H2 cyclotrimerization.